A Tafseer Study on Qurâ€™an Reading in the Tradition of the Banyumas Muslim Community - Naqiyah Naqiyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2021)
This paper examined the interpretation of ngaji (reading al-Qurâ€™an) in the traditions of Banyumas people. This research was conducted by a survey method through interactive interviews with several persons who read the Qurâ€™an in Banyumas. The data were then analyzed by using the typology of worshipers. The results showed that reading the Qurâ€™an has different interpretations depending on the community views of how to read and the purpose of reading it. Reading the Qurâ€™an in the Banyumas community is unique depending on the community traditions and social events and the interaction patterns of their daily life. Furthermore, read- ing the-Qurâ€™an is believed to be able to calm their soul, to become a medicine, to protect from the disturbances of other creatures, and to become a part of the rites of life (from birth to death). They obtained these beliefs from scholars, clerics, teachers, and from their social communication as well as from their own spiritual and empirical experiences. We concluded that reading the Qurâ€™an for the Banyumas people tended to be â€œhoping for Godâ€™s graceâ€ directly, in other words, they were being in the tujjar (merchant) type worshipers.